Studi Komparasi Model Pembelajaran Kooperatif Think Pair Square dengan Model Pembelajaran Kooperatif Student Teams Achievement Divisions terhadap Hasil Belajar Fisika - Sriwahyuninsi Sriwahyuninsi; Amiruddin Hatibe; Kamaluddin Kamaluddin (Universitas Tadulako, 2021)
The purpose of this study was to determine the differences in physics learning outcomes between classes using the Think Pair Square cooperative learning model and the Cooperative Student Teams Achievement Divisions. The research method used is a quasi-experimental, with a research design